O caminho para o futuro: ações da United States Information Agency (USIA) na Guerra Fria (1953-1968) - Marangoni, Adriano J (2015)
At the end of the 2nd World War, the information and intelligence services used by the United States have gone through several redesigns. One result was the creation of the United States Information Agency in August 1953. This agency, according to guidelines established by the US Congress and President Dwight Eisenhower, had the mission to promote a better understanding between the United States and other nations of the world. In practice, the actions of this agency were directly linked to the characteristics and requirements imposed by the Cold War. The USIA was ruled by the opposition of the United States against the Soviet Union and Communism. In this war, art, literature, the media, and science, among many other cultural expressions were pooled and mobilized on behalf of a political, ideological and even philosophical project. From a historical perspective, one can recognize that this "project", diffuse and fragmented in the design of its founders, contained a homogeneous civilization matrix, visible in the various agency's practices over the years. While factors such as the improvement of military weapons, expansion and armies employment constituted as a fact throughout the world, culture, in the hands of cultural officers of the US Information Agency, was used in almost equal terms. While the barbarity of violence which was one inescapable horizon of possibility, a conception of civilization was settled alternatively, a path for the future